RA10.05: CHEMORADIOTHERAPY IMPROVES LOCO-REGIONAL CONTROL AND DISEASE-FREE SURVIVAL OVER CHEMOTHERAPY IN OESOPHAGEAL ADENOCARCINOMA WITH SIGNET RING MORPHOLOGY. (14th September 2018) - Van Hootegem, Sander; Smithers, Mark; Gotley, David; Thomson, Iain; Brosda, Sandra; Thomas, Janine; Gartside, Michael; Wijnhoven, Bas P L; Van Lanschot, J J B; Lagarde, Sjoerd M; Barbour, Andrew
Abstract: Background: The presence of signet ring cells (SRC) is associated with poorer survival in multiple cancer types. Here we aimed to determine the predictive and prognostic value of SRC in oesophageal and junctional adenocarcinoma (OAC) for patients treated with neoadjuvant chemoradiotherapy (nCRT) or chemotherapy (nCT). Methods: Patients who underwent nCRT and nCT followed by surgery for OAC between 2000 and 2016 were identified from two institutional prospective databases. Pre-treatment biopsy and surgical resection pathology reports were used to determine the presence of SRC morphology. The association between SRC histology and clinicopathological characteristics including pathological response was assessed. The prognostic impact of SRC on disease-free survival (DFS) and overall survival (OS) was determined. Survival was calculated with Kaplan Meier method and differences tested with log rank test. Results: Of the 689 study patients, 129 had SRC (nCRT; n = 65, nCT; n = 64) and 560 patients had no evidence of SRC (nCRT; n = 326, nCT; n = 234). The SRC group had higher pT stage ( P = 0.004) and median number of involved nodes ( P = 0.004) following nCT compared with the non-SRC group. There were no significant differences between the two groups with respect to age, gender, tumour site, pN, R status or pathological complete response. For the 129 in the SRC group, nCT patients had significantly worse DFS (median [IQR]; 12 months [50–5]) compared with nCRT patients (median [IQR]; 26 months [111–9], P = 0.021). Moreover, nCT had a worse loco-regional recurrence-free survival ( P  = 0.004), but not distant recurrence-free survival ( P = 0.74), in the SRC group. In contrast, there were no differences in DFS ( P = 0.245) or recurrence patterns between nCRT and nCT among the 560 non-SRC patients. However, there was no significant difference in OS according to SRC status following nCT ( P = 0.076) or nCRT ( P = 0.541). Conclusion: For SRC OAC, nCRT is associated with better DFS and loco-regional control compared with nCT. However, the presence of SRC in OAC was not prognostic for OS following nCT or nCRT. Disclosure: All authors have declared no conflicts of interest.